Assessment on Medowo Village Kandangan District, Kediri Regency as Biogas Based Energy Independent Village - Wahyu Devi Hapsari Wijayanti; Surjono; Hartati Kartikaningsih (Postgraduate, University of Mataram, 2025)
National energy security can be achieved by improving energy security at the village scale. Village energy independence can be achieved if at least 60% of the village's energy needs can be met by utilizing local energy potential. To determine the energy independence of a village, it is necessary to collect data on total energy usage and the potential generation of existing energy source. Medowo Village was chosen as a case study because this village actively use biogas as energy source for cooking. This study was conducted using a mixed method approach with an explanatory sequential design type. The descriptive method is used to describe the condition of energy supply in Medowo Village. The quantitative method is used to determine the condition of supply-demand and the potential for biogas generation. Primary data collection was carried out through questionnaires and direct observation at the location. Meanwhile, secondary data collection was obtained from literature studies, KUD Kertajaya, and related government agencies. It was found from the study that current biogas production only reach 40.31% of the theoretical biogas production potential. As for total energy mix, biogas contribution is 15,37%. Therefore alternatives are offered to achieve energy independence by paying attention to problems encountered during research.